Quantitative SUMO-1 modification of a vaccinia virus protein is required for its specific localization and prevents its self-association - Palacios, Silvia; Perez, Laurent H.; Welsch, Sonja; Schleich, Sibylle; Chmielarska, Katarzyna; Melchior, Frauke; Krijnse-Locker, Jacomine (Molecular biology of the cell, 2005)
Vaccinia virus (VV), the prototype member of the Poxviridae, a family of large DNA viruses, carries out DNA replication in specialized cytoplasmic sites that are enclosed by the rough endoplasmic reticulum (ER). We show that the VV gene product of A40R is quantitatively modified by SUMO-1, which is required for its localization to the ER-enclosed replication sites. Expression of A40R lacking SUMO-1 induced the formation of rod-shaped cytoplasmic aggregates. The latter likely consisted of polymers of nonsumoylated protein, because unmodified A40R interacted with itself, but not with the SUMO-1-conjugated protein. Using a bacterial sumoylation system, we furthermore show that unmodified A40R is mostly insoluble, whereas the modified form is completely soluble. By electron microscopy, the A40R rods seen in cells were associated with the cytosolic side of the ER and induced the apposition of several ER cisternae. A40R is the first example of a poxvirus protein to acquire SUMO-1. Its quantitative SUMO-1 modification is required for its proper localization to the viral “mini-nuclei” and prevents its self-association. The ability of the nonsumoylated A40R to bring ER membranes close together could suggest a role in the fusion of ER cisternae when these coalesce to enclose the VV replication sites.
Gesehen am 06.09.2023